Heavy metals, antibiotics and nutrients affect the bacterial community and resistance genes in chicken manure composting and fertilized soil. (1st March 2020) - Deng, Wenwen; Zhang, Anyun; Chen, Shujuan; He, Xueping; Jin, Lei; Yu, Xiumei; Yang, Shengzhi; Li, Bei; Fan, Liangqian; Ji, Lin; Pan, Xin; Zou, Likou
Abstract: Succession of bacterial communities involved in the composting process of chicken manure, including first composting (FC), second composting (SC) and fertilizer product (Pd) and fertilized soil (FS), and their associations with nutrients, heavy metals, antibiotics and antibiotic resistance genes (ARGs) were investigated. Firmicutes, Proteobacteria, Bacteroidetes, and Actinobacteria were the dominant phyla observed during composting. Overall, potential pathogenic bacteria decreased from 37.18% (FC) to 3.43% (Pd) and potential probiotic taxa increased from 5.77% (FC) to 7.12% (Pd). Concentrations of heavy metals increased after second composting (SC), however, no significant differences were observed between FS and CS groups. Alpha diversities of bacterial communities showed significant correlation with heavy metals and nutrients. All investigated antibiotics decreased significantly after the composting process. The certain antibiotics, heavy metals, or nutrients was significantly positive correlated with the abundance of ARGs, highlighting that they can directly or indirectly influence persistence of ARGs. Overall, results indicated that the composting process is effective for reducing potential pathogenic bacteria, antibiotics and ARGs. The application of compost lead to a decrease in pathogens and ARGs, as well as an increase in potentially beneficial taxa and nutrients in soil. Highlights: Compost is effective for reducing pathogenic bacteria, antibiotics and ARGs. Antibiotics, heavy metals and nutrients could affect bacterial community and ARGs. Heavy metals in chicken manure is the main factor that affects bacterial composition. The application of compost lead to a decrease in pathogens and ARGs in soil.